2013
DOI: 10.4236/wja.2013.32022
|View full text |Cite
|
Sign up to set email alerts
|

Partnering with Batswana Youth and Families for HIV and AIDS Prevention

Abstract: Introduction: This qualitative study triangulated data from adolescents, parents, and key informants in Gaborone, Botswana on adolescents' risks for HIV infection, STIs and pregnancy, the types of relationships they get into, and preventive measures they use to protect themselves against HIV infection. The goal of this qualitative research is to inform adaptation of an intervention originally developed, implemented, and evaluated in the US that was effective in reducing the risk of HIV infection and early preg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
(14 reference statements)
0
4
0
Order By: Relevance
“…Among African–American adolescent grandchildren raised by grandmothers, they are more likely than children raised by their parents to engage in unprotected sexual intercourse (Minkler & Fuller‐Thompson, ), but this has not been assessed among Africans. Prevalence of HIV‐related risk behaviours among adolescents in Botswana is high and continues to grow, and the risks include poor parental monitoring and poor parent and adolescent communication on sexual matters (Seloilwe et al ., ) and limited or non‐existent communication on sexual issues among parents and adolescents (Seloilwe et al ., ). There are limited data on grandparent–grandchild sexual communication processes, yet many studies have been carried out on sexual communication among parents and their adolescent children (Cornelius et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Among African–American adolescent grandchildren raised by grandmothers, they are more likely than children raised by their parents to engage in unprotected sexual intercourse (Minkler & Fuller‐Thompson, ), but this has not been assessed among Africans. Prevalence of HIV‐related risk behaviours among adolescents in Botswana is high and continues to grow, and the risks include poor parental monitoring and poor parent and adolescent communication on sexual matters (Seloilwe et al ., ) and limited or non‐existent communication on sexual issues among parents and adolescents (Seloilwe et al ., ). There are limited data on grandparent–grandchild sexual communication processes, yet many studies have been carried out on sexual communication among parents and their adolescent children (Cornelius et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…In order to reduce adolescents’ hesitancy to talk with their parents about sexual matters, interventions could be delivered separately, in parallel, to adolescents and parents, with structured opportunities for them to come together. This approach would be highly congruent with the desires expressed by both parties (Seloilwe et al, 2013).…”
Section: Discussionmentioning
confidence: 93%
“…These findings are congruent with previous research about cultural norms in Botswana that noted Batswana tend to avoid discussions about sexuality between parent and child (Denbow & Thebe, 2006; Ntsayagae et al, 2008). Additional research has found that both parents and adolescents expressed a desire to be able to discuss sensitive topics with one another, but felt they do not have adequate knowledge or communication skills and were hesitant to do so (Fehringer et al, 2013; Nam et al, 2009; Seloilwe et al, 2013; St. Lawrence et al, 2013), which may explain why adolescents perceived low parental responsiveness to discussing sensitive issues.…”
Section: Discussionmentioning
confidence: 99%
“…In qualitative interviews with male ( N = 20) and female ( N = 20) Botswana adolescents 13 to 19 years (average age was 15.3), an unexpectedly high proportion reported receiving sexual initiations from adults offering desirable goods in exchange for sex (Seloilwe et al, 2013; St Lawrence et al, 2013). Participants from urban and peri-urban areas and high-, moderate-, and low-income neighborhoods were purposively recruited from schools and youth-focused programs.…”
Section: Methodsmentioning
confidence: 99%